Medidas radiológicas útiles en patología músculo esquelética cotidiana - Miranda G., Gonzalo; Díaz J., Jorge (Revista Hospital Clínico Universidad de Chile, 2009)
There are multiple and diverse measurements described in medical literature that can be used for the radiological assessment of osteoarticular pathology. These are presented in regards to simple radiography as well as in computed tomography (CT) and Magnetic Resonance (MRI). However, this great diversity of available measurements has lead to a paradoxical and undesirable sub-utilization of these measurements in our daily practice. On the other hand, it is paramount that those measurements are recognized by other radiologists as well as by traumatological teams. An adequate interdisciplinary agreement is thus achieved. These days, with the use of digital radiology, conducting radiological measurements, drawing lines and assessing degrees, result in a fast and easy-to-use tool, provided it is adequately know. This revision presents an outline on the main radiological measurements used to evaluate osteoarticular pathology. These measurements are universally known and do not present major difficulties in their execution or interpretation.